The influence of Accrual Quality, Accounting Conservatism and Debt Maturity on Investment Efficiency: The influence of Accrual Quality, Accounting Conservatism and Debt Maturity on Investment Efficiency - Rosalina, Eka (Yayasan Ilomata, 2024)
ABSTRACT: A company's investment decisions and their results determine a company's future cash flows and profitability and have a profound effect on a company's long-term survival and growth. Investment optimization must be made because it is the most important responsibility of management and a fundamental problem in corporate finance. A company's investment decisions and their results determine the company's future cash flow and profitability and have a profound effect on the company's survival, appropriate long-term growth and achieving investment efficiency in the company. This research aims to examine the accrual quality, accounting concervatime and debt maturity on investment efficiency. This test was carried out in a regression manner on manufacturing companies in Indonesia and the sample size was 132 out of 174 populations that met the criteria during the 2019 to 2021 fiscal period. The results show that the results of testing the quality of financial reports with Accrual Quality have a positive effect on investment efficiency, indicating that the quality of financial reports a higher source of information and will reduce asymmetric information thereby increasing investment efficiency And also debt maturity does does not have a significant effect on investment efficiency, because the cash flow that would otherwise be desirable to invest must ultimately be spent on debt maturity which is quite high Keywords: Accrual Quality, Accounting Concervatism and Debt Maturity on Investment Efficienc